Genetic Determination of Bronchopulmonary Dysplasia Formation: Pros and Cons - V. K. Pozharishchenskaya; I. V. Davydova; K. V. Savostianov; L. S. Namazova-Baranova; E. B. Pavlinova; A. V. Pushkov (Педиатрическая фармакология)
Currently, researches are being actively carried out to identify genetic risk factors for the development of bronchopulmonary dysplasia (BPD) in premature infants, including genetic polymorphism encoding surfactants, matrix metalloproteinases, cytokines, growth factors, and components of the body’s antioxidant defence. The review presents the results of foreign and domestic genetic trials in this field aimed at predicting the possible formation of BLD in premature infants and providing a personalized approach to the management of such patients.